Financial Independence Perspective of Surah Al-Baqarah - Fatimatuzzahra; Misbahul Munir (Penerbit Hellow Pustaka, 2024)
A key component of both individual and collective life is financial literacy, and Surah Al-Baqarah in Islam offers comprehensive instructions on managing money. With a focus on concepts like zakat, sedekah, and the use of discretion in daily budget distribution, this essay explores the idea of financial management from the viewpoint of Surah Al-Baqarah. In this context, the study describes how careful lending and saving practices combined with a study of the Qur'an can help people become financially independent. In order to achieve behavioral and financial stability, this analysis provides insightful information to the Islamic society as well as to individuals.